The Threat of Financial Contagion to Emerging Asia's Local Bond Markets: Spillovers from Global Crises - Iwan J. Azis; Sabyasachi Mitra; Anthony Baluga; Roselle Dime (Asian Development Bank (ADB), 2013)
This paper employs multivariate GARCH models with a BEKK specification to show significant shock and volatility spillovers from mature bond markets into select emerging Asian local currency bond markets. Results reveal that while the growth of individual bond markets in recent years has been impressive, the threat of financial contagion to emerging Asian bond markets from shock and volatility spillovers in mature markets is real. Although emerging Asian local bond market volatilities are more determined by their own respective shocks and volatilities, in some markets the direct shock and volatility spillovers remain significant. An extended analysis also shows indirect spillovers within domestic asset markets and across economies. The results have important implications for the monitoring and coordination of policies, not just within national jurisdictions but also in regional and global settings, in order to maintain financial stability.
hdl:11540/2334
Keywords: C14; E43; E62; G12; G12; H62; 330; Spillovers; contagion; sovereign bond yields and returns; conditional volatility; emerging Asian local currency bond markets; financial crisis; Finanzkrise; Internationaler Finanzmarkt; Ansteckungseffekt; Öffentliche Anleihe; Volatilität; Rendite; Rentenmarkt; Schwellenländer; Asien